How important are capital controls in shaping innovation activity?. (March 2023) - Bechlioulis, Alexandros; Economidou, Claire; Karamanis, Dimitrios; Konstantios, Dimitrios
Highlights: Capital controls shape innovation activity through the finance of R&D investment. An inverse U-shaped relationship is documented between capital controls and R&D. Composition of individual asset restrictions in capital controls index matters. Equity-based finance restrictions are found to greatly shape both R&D and patents. Credit (bank) and direct investment asset restrictions exert no effect. Abstract: This paper studies the role of capital controls in shaping innovation activity through the finance of R&D investment. The paper offers insights into the real effects of financial sector on the economy. It first asks whether capital controls shape innovation activity, both from the input (R&D) and output (patents) side. Based on a large dataset that includes 53 developed and emerging countries over the period 1996–2016 and a fixed effects identification and appropriate instrumentation strategy, results support a robust inverse U-shaped relationship between capital controls and R&D. Capital restrictions can be beneficial for R&D investment till a certain point and thereafter have detrimental negative effects, particularly for patents. Second, it asks whether the composition of restrictions of individual assets in the aggregate capital control index matters. We find equity-based finance restrictions greatly shape innovation activity, whereas controls on credit (bank) and direct investment assets exert no effect.